Evaluation of PHEIC (Public Health Emergency of International Concern) Detection Implementation on The Performance of Port Health Employees Class I Medan - Rakhmad Kurnia Putra Parinduri; Ismail Efendy; Asriwati Amirah (Journal La Medihealtico, 2021)
Public health emergencies can occur imported i.e. the source of the emergency comes from outside the region and the epicenter is the source of the emergency comes from the work area. Both conditions can arise in unpredictable situations so that the ability of the government and stakeholders in preventing, detect early to detect, handle cases as early as possible to response will affect the extent of the magnitude of emergency event sand post-event handling. Readiness surveillance device in the face of the influx of infectious diseases. Early detection efforts are carried out by detecting events through examination and screening, information and Verification of passengers, transport and disease risk factors. This type of research is Descriptive with the aim to know the evaluation of the implementation of PHEIC to the performance of Class I Medan Port Health Office in 2020, based on respondent answers. The population is all quarantine officers in the working area of Class I MPA Medan as many as 58 respondents, sampling using total sampling. The result of research shows that based on respondent answers obtained PHEIC implementation with employee discipline obtained there is still no timely out hours of work and never reprimanded directly by superiors, while supervision is still less than the leadership is more considered objectively and thoroughly, work activities organized together in teams not individually. It is recommended to all employees to enforce discipline, especially at work hours and the need for effective staffing in improving employee performance as well as working based on a predetermined team work.